Coupling finite volume and lattice Boltzmann methods for pore scale investigation on volatile organic compounds emission process. (October 2015) - Mu, Yu-Tong; Chen, Li; He, Ya-Ling; Tao, Wen-Quan
Abstract: A coupled numerical model is employed to investigate the emission process of volatile organic compounds (VOCs) in the building material and chamber. In this model, for the first time the Langmuir-isotherm sink model is introduced by taking into account of the adsorption/desorption process between the absorbed VOCs on the material surfaces and the gas phase VOCs in pores. The porous material adopted in the model is reconstructed with a random generation-growth algorithm for 3D microstructures fibers. This model is numerically implemented by a multiscale strategy with the lattice Boltzmann method (LBM) being used to simulate pore-scale diffusion and finite volume method (FVM) for macroscopic transport. Information transferring from the macro scalar obtained from FVM zone to the distribution functions in LBM zone is executed with a reconstruction operator. The model is validated with the well-mixed diffusion model, and then applied to predict the VOCs emission process. A comprehensively investigation of the effects of sorption parameters, including adsorption/desorption rate constants, partition coefficient, Schmidt number and Reynolds number on the VOCs adsorption/desorption process in building material and emission process in chamber is conducted. The simulation results reveal that the equilibrium VOCs concentration in the building material pores could be numerically estimated with our proposed model; the equilibrium concentration of VOCs in a closed chamber depends on the initial emitted VOCs concentration and partition coefficient; Reynolds number can promote the emission process in a ventilated chamber. Graphical abstract: Highlights: A multi-scale coupled method is proposed to investigate VOCs emission process. Sorption between adsorped and gas phase VOC is firstly considered at pore-scale. Sorption rate constants influence the initial equilibrium VOC concentration. VOC concentration in chamber decreases with partition coefficient. Schmidt number shortens the time to reach an equilibrium state in building material.